A Randomized Comparison of the Effect of Slow/Gradual and Sudden Balloon Deflation Angioplasty on Early Outcomes of Stable Patients Undergoing Elective Native SingleVessel Percutaneous Coronary Intervention. Issue 2 (December 2019) - Balin, Mehmet
No abstract available